Multisensory Approach-Oriented Teaching Materials to Improve Elementary School Students' Basic Reading Concepts - I Wayan Eka Mahardika; Ni Nyoman Kurnia Wati; I Made Sedana (Universitas Pendidikan Ganesha, 2025)
The low mastery of basic reading concepts among second-grade elementary school students remains a major problem in learning, one of which is the use of teaching materials that do not accommodate differences in student learning styles. Therefore, a study is needed to evaluate the effectiveness of multisensory teaching materials in improving basic reading concepts among second-grade elementary school students. This study aims to analyse the effectiveness of multisensory teaching materials in improving second-grade elementary school students' basic reading concepts. The research subjects were 35 students selected through total sampling. The study used a one–group pretest–posttest design, with data collected via basic reading concept tests administered before and after the implementation of the teaching materials. Analysis was carried out using descriptive statistics and Paired Sample t-Test after the data met the requirements of normality and homogeneity. The results showed that the use of multisensory teaching materials significantly improved second-grade students' basic reading concepts, as indicated by higher posttest scores in the experimental class than in the control class. In conclusion, multisensory-oriented teaching materials are effective in improving basic reading concepts among second-grade elementary school students, thereby addressing the problem of low initial reading abilities. This research implies that the use of learning media that combine visual, audio, and kinesthetic stimulation can be an alternative strategy to support more meaningful reading instruction in elementary schools.